The effect of prebiotic and probiotic food consumption on anxiety severity: a nationwide study in Korea - Tae, Hyejin; Kim, Tae-Suk (Frontiers in Nutrition, 2024)
Objectives: Over the past decade, research has reported that diet and gut health affect anxiety symptoms through changes in the gut microbiota. Therefore, the introduction of prebiotic and probiotic food favorable for the intestinal microbiota is necessary to improve the mental health of the host. The purpose of this study was to examine the contribution of prebiotic and probiotic foods to lowering anxiety symptoms using a large, nationwide population-based database. Materials and methods: The study population included 4,317 individuals 19 to 64 years of age who participated in the Korean National Health and Nutrition Examination Survey (KNHANES Ⅷ-3, 2019-2021). A food frequency questionnaire was used to evaluate prebiotic and probiotic food consumption. The Generalized Anxiety Disorder Assessment 7-item scale (GAD-7) assessed the severity of anxiety symptoms. The effect of prebiotic and probiotic food consumption on anxiety severity was analyzed using multiple logistic regression. Results: Anxiety symptom severity was significantly lower in the highest prebiotic and/or probiotic food consumption tertiles compared to the lowest food consumption tertile. We also found a sex difference in the odds ratio for anxiety symptoms. The consumption of prebiotic food was significantly associated with the highest odds of anxiety among both men and women. However, probiotic food had a significant beneficial effect on lowering anxiety symptoms in men but not in women. Conclusions: Our finding suggests that prebiotic and probiotic food consumption might confer a beneficial influence on anxiety symptoms. Further research is required for a deeper understanding into the mechanisms of the positive effects of prebiotics and probiotics on anxiety.